Analysis of Vitamin C Content and Preferences for Modisco Pudding with the Addition of Crystal Guava Juice (Psidium guajava L Cultivar Kristal) - Rohmawati, Ninna; Farikha, Tera R.; Akbar, Abdul Azis (Current Nutrition & Food Science, 2024)
Background: Indonesia has made progress in achieving the target of reducing malnutrition cases, but 10.2% are still malnourished, according to data from The Global Nutrition Report 2020. Intake of micronutrients, one of which is vitamin C, affects the incidence of malnutrition cases. Vitamin C has the function of maintaining health through the immune system. One supplementary feeding program that can overcome cases of malnutrition is Modified Dietetic Skimmed Milk and Coconut Oil (Modisco). Modisco's reception is not very good, especially for toddlers, because it is in the form of liquid. Modisco pudding, with the addition of crystal guava juice, aims to improve the taste and increase the nutritional value of Vitamin C. Objective: The objective of the study is to analyze the content of Vitamin C in the preference test of Modisco pudding with the addition of crystal guava juice at 0%, 15%, 30%, and 45% concentration. Methods: This study used a quasi experimental design involving 4 treatments and 3 replications. The research subjects were 25 panelists of elementary school students. Results: The results showed the levels of Vitamin C in various proportions to be significantly different (p ≤ 0,05). The results of the preference test showed significant differences in the color, aroma, taste, and texture of the modisco pudding with the addition of crystal guava juice (p ≤ 0,05). Conclusion: The results showed that with more addition of crystal guava juice, the level of vitamin C increased, but the level of preference decreased. The most preferred Modisco pudding was X1 (addition of 15%) with a vitamin C content of 14,4 mg.
Keywords: crystal guava juice